Targeting the tumour microenvironment in ovarian cancer. (March 2016) - Hansen, Jean M.; Coleman, Robert L.; Sood, Anil K.
Abstract: The study of cancer initiation, growth, and metastasis has traditionally been focused on cancer cells, and the view that they proliferate due to uncontrolled growth signalling owing to genetic derangements. However, uncontrolled growth in tumours cannot be explained solely by aberrations in cancer cells themselves. To fully understand the biological behaviour of tumours, it is essential to understand the microenvironment in which cancer cells exist, and how they manipulate the surrounding stroma to promote the malignant phenotype. Ovarian cancer is the leading cause of death from gynaecologic cancer worldwide. The majority of patients will have objective responses to standard tumour debulking surgery and platinum-taxane doublet chemotherapy, but most will experience disease recurrence and chemotherapy resistance. As such, a great deal of effort has been put forth to develop therapies that target the tumour microenvironment in ovarian cancer. Herein, we review the key components of the tumour microenvironment as they pertain to this disease, outline targeting opportunities and supporting evidence thus far, and discuss resistance to therapy.